Blood & kinship matter for metaphor from ancient Rome to the present - Johnson, Christopher H.; Jussen, Bernhard; Sabean, David Warren; Teuscher, Simon (Berghahn Books, 2013)
Blood awakens associations with ancient ideas. But we know very little about the historical representations of blood in Western cultures. The contributors attempt to follow the use of blood in mapping family and kinship relations in European culture from the ancient world to the present.